Student's Difficulties In Mastering English Pronunciation - Sitompul, Eby Delyani; Hasibuan, Maisyaroh; Nasution, Sania Oktavia; Aulia, Winda; Santoso, Didik (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
The purpose of this study is to address the problem of incorrect pronunciation among students studying English education. The study used a descriptive methodology. Five students from the English education department participated in this study. Through interviewing and test recordings, the data was gathered. A test was used to evaluate the problems that students were facing, and an interview was done to validate the information gathered. Due to the differences in the linguistic systems of English and Bahasa, there were problems with pronunciation such as irregular placement and articulation, as well as a deficiency in the ability to pronounce vowels and consonants according to the international phonetics alphabet. The professor offered oral comments, mobile phone apps, audio-visual materials, and a lot of reading practice as methods for teaching English pronunciation.